METODE ROLE PLAYING SEBAGAI ALTERNATIF PEMBELAJARAN KETERAMPILAN DRAMA DI SEKOLAH DASAR - Julianto, Indra Rasyid; Saputro, Pramisdi Winanto; Hayati, Rifa'atussalwa; Gusvita, Widya; Sintasari, Diardana Prima (PT. CASA CENDEKIA MEDIA, 2025)
This research proposes the use of role-playing as an alternative method for teaching drama skills in elementary schools, employing a literature review methodology. The concept of role-playing is grounded in proven educational theories, particularly Lev Vygotsky's emphasis on social interaction in learning. Constructivist approaches and Jean Piaget's child development theory also provide relevant foundations for developing drama skills through role-playing. Drama skills play a crucial role in shaping students' characters, boosting confidence, and instilling moral values. Implementation challenges for teaching drama skills in elementary schools include teachers' lack of understanding, resource limitations, academic pressure, and concerns related to assessment. Nevertheless, the role-playing method offers significant potential in engaging students, enhancing creativity, and improving communication skills. By incorporating these aspects, role-playing emerges as an effective and efficient method for teaching drama skills at the elementary school level.